Cost and return of rice cultivation in Assam - Pegu, Nijan Chandra; Singha , Anuradha (Journal of Postharvest Technology, 2022)
In India, looking at the different components of the rural economy, agriculture remains the mainstay of the rural sector. Agriculture in Assam is popularly known as rice culture, because it is dominated by rice as the most important cereal crop in terms of area, production and productivity. The study has examined the cost and returns of rice cultivation in Assam. It is found that the large size farmers had highest rate of gross margin followed by medium marginal and small farmer per hectare. The large farmers found to be highest profitable because of fact that they could properly and economically expenditures on inputs as well as per hectare of yield has found to be high in the study area.